Nintedanib in the management of pulmonary fibrosis after COVID-19: a case report (BIRDEM Medical Journal, 2021)
Pulmonary fibrosis is becoming a recognized complication of coronavirus disease 2019 (COVID-19). Patients with pulmonary fibrosis may present with dry cough, shortness of breath, nail clubbing, low oxygen saturation. We report a case of a 40-year-old male patient with pulmonary fibrosis due to COVID- 19. Clinical examination showed that the patient was dyspneic with low oxygen saturation and there was bilateral inspiratory crepitation in the lower part of his chest. High resolution computed tomography showed bilateral multifocal patchy ground-glass opacities, consolidation with peripheral and basal distribution, sub-pleural fibrotic bands and vascular thickening (almost 40-45% of parenchymal involvement). We prescribed him an antifibrotic drug, nintedanib and there was a significant clinical and radiological improvement after 15 days of treatment. Nintedanib may have novel therapeutic role in preventing COVID-19 associated fibrosis.Birdem Med J 2021; 11(2): 148-152